Sensory aspects of liquid smoking of giant river prawn: comparison with traditional smoking - Portella, Carolina G. [UNESP]; Sant'Ana, Lea S. [UNESP]; Valenti, Wagner Cotroni [UNESP] (Wiley-Blackwell, 2011)
P>The purpose of this paper is to investigate the impact of liquid smoke on the sensory characteristics of giant river prawn (Macrobrachium rosenbergii). The sensorial profile was plotted using quantitative descriptive analysis and assessment of the acceptability of samples of beheaded and peeled and only beheaded freshwater prawns smoked using the traditional method or liquid smoke (LS). The prawns subjected to LS were characterised by their aroma, artificial flavour and bitter flavour. The beheaded, peeled prawns were found to be more acceptable, confirming that the presence of the shell is a limiting factor in the acceptability of smoked prawns.
Keywords: Liquid smoke; Macrobrachium rosenbergii; quantitative descriptive analysis; sensory analysis